2021
DOI: 10.1111/tid.13615
|View full text |Cite
|
Sign up to set email alerts
|

Detection of BK polyomavirus genotypes to predict the development of BK polyomavirus‐associated complications in kidney transplant recipients: A retrospective analysis

Abstract: Objectives: This study focused on the role that BK polyomavirus (BKPyV) genotypes can play in the development of BKPyV-associated complications in renal transplant recipients. Methods: A retrospective observational study (January 2015 to April 2018) was conducted by analyzing BKPyV genotypes in 180 blood samples with detectable BKPyV viral load (VL) > 1000 copies/mL, from 63 renal transplant recipients. VL and BKPyV genotypes detections were based on real-time PCR (rt-PCR)-specific assays. Results: Forty-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…1 BKV can cause serious complications, such as hemorrhagic cystitis (HC) after hematopoietic stem cell transplantation (HSCT) and BKV-associated nephropathy due to allograft loss after renal transplantation. [1][2][3][4] The frequency of BKV-associated HC (BKV-HC) after HSCT is ∼10%. 1,2 BKV-HC reduces patients' quality of life and may lead to decreased overall survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 BKV can cause serious complications, such as hemorrhagic cystitis (HC) after hematopoietic stem cell transplantation (HSCT) and BKV-associated nephropathy due to allograft loss after renal transplantation. [1][2][3][4] The frequency of BKV-associated HC (BKV-HC) after HSCT is ∼10%. 1,2 BKV-HC reduces patients' quality of life and may lead to decreased overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…BK polyomavirus (BKV) infects most of the general population during childhood and persists in renal tubular cells and urothelial cells 1 . BKV can cause serious complications, such as hemorrhagic cystitis (HC) after hematopoietic stem cell transplantation (HSCT) and BKV‐associated nephropathy due to allograft loss after renal transplantation 1–4 . The frequency of BKV‐associated HC (BKV‐HC) after HSCT is ∼10% 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the sequences revealed co-infection with genotypes I and IV in 8% of DBDs (4/49). Co-infections with different genotypes have previously been described by Muñoz-Gallego et al [ 41 ], who observed mixed genotypes in more than half of patients tested (33/63), among which the most common was the combination of genotypes I and II. The researchers noted that patients with mixed genotypes developed a detectable BKPyV viral load in blood (VL > 1000 copies/mL) more rapidly and had a greater risk of clinical manifestations associated with BKPyV infection.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, we found a high prevalence of BKV-II subtype (25% of BKVN diagnostic samples), which had already been found in another recent study in Spain. 27 This may be due to the fact that almost a third of our study population originated from Africa, a region where the prevalence of BKV-II is higher compared to Europe, Northern America, or Asia. 7 Moreover, VP1 sequencing identified the same BKV-subtype in all plasma samples, from the onset of BK viremia to BKVN.…”
Section: Discussionmentioning
confidence: 97%